Analisis terhadap Putusan Mahkamah Konstitusi Nomor 30/PUU-XVI/2018 Terkait Larangan Pencalonan Anggota Dewan Perwakilan Daerah (DPD) dari Fungsionaris Partai Politik - Attamimi, Bati Mulia; Suranto, Suranto (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis study aims to determine how the requirements for nominating a member of the Regional Representative Council and the consideration of judges in passing Decision Number 30 / PUU-XVI / 2018. The results of the research show that the requirements for nominating members of the Regional Representative Council are as stipulated in Article 182 of Law Number 7 of 2017 concerning General Elections and the consideration of Judges in the Decision of the Constitutional Court Number 30 / PUU-XVI / 2018, violating 2 (two) principles attached to the Constitutional Court’s post, namely the erga omnes principle and the legislative negative principle.Keywords: constitutional court; regional representative council.